Proving Liveness of Parameterized Programs - Farzan, Azadeh; Kincaid, Zachary; Podelski, Andreas (Proceedings of the 31st Annual ACM/IEEE Symposium on Logic in Computer Science, 2016)
Correctness of multi-threaded programs typically requires that they satisfy liveness properties. For example, a program may require that no thread is starved of a shared resource, or that all threads eventually agree on a single value. This paper presents a method for proving that such liveness properties hold. Two particular challenges which are addressed in this work are that (1) the correctness argument may rely on global behaviour of the system (e.g., the correctness argument may require that all threads collectively progress towards "the good thing" rather than one thread progressing while the others do not interfere), and (2) such programs are often designed to be executed by any number of threads, and the desired liveness properties must hold no matter how many threads are active in the system.